Posttraumatic pseudoaneurysm involving the superficial temporal artery in a pediatric patient - Kylie Disch; Jason McKee (Elsevier, 2021)
Introduction: Superior temporal artery pseudoaneurysms were first described by Thomas Bartholin in 1740, and since then approximately 400 cases have been reported in the literature. It is estimated that of aneurysms that are surgically repaired, traumatic aneurysms, pseudoaneurysms, and arteriovenous (AV) fistulas of the superficial temporal artery (STA) account for 0.5%-2.0%. Of these, only a few reported are in the pediatric population. Case: An otherwise healthy 16-year-old male presented to UNM Pediatric Surgery Clinic with a small temporal mass in January 2020. He had previously been punched in the side of the head in August 2019 and noticed the mass after the bruising and swelling in the area had subsided. The mass was then determined to most likely be a posttraumatic pseudoaneurysm of the temporal artery, based on exam showing a 1 cm soft, mobile, pulsatile mass. A CT angiogram of the head and neck confirmed. Observation, IR intervention, and surgical removal were discussed with the patient and his mother in clinic, and they opted for surgical removal. In February 2020, he underwent an excision of left superficial temporal artery pseudoaneurysm under general anesthesia. Intraoperatively, it was noted that a part of the superficial temporal vein was densely adherent to the pseudoaneurysm, and was small inferior to the pseudoaneurysm, and engorged superiorly, concerning for a possible fistula formation. This was not confirmed intraoperatively, but a portion of the left superficial temporal vein had to be excised as there was no clear plane between the pseudoaneurysm and the vein. Pathology results did not demonstrate a fistula formation, but did confirm a pseudoaneurysm of the STA.